PENENTUAN UMUR SIMPAN MINUMAN FUNGSIONAL SARI AKAR ALANG – ALANG DENGAN METODE ACCELERATED SHELF LIFE TESTING (ASLT) (Studi Kasus di UKM “R.ROVIT” Batu - Malang) - Hesti Anagari; Siti Asmaul Mustaniroh; Wignyanto Wignyanto (AGROINTEK, 2011)
This study aims to determine the shelf life of reed roots extracts beverages with Accelerated Shelf Life Testing (ASLT) method based on Arrhenius model, the model equations to express the relationship of temperature on the level of product damage. Determining shelf life by using the Accelerated Shelf Life Testing (ASLT) is done by speeding up the process of degradation or reaction in the experiment, namely raising the storage temperature on some level temperature above room temperature, thus speeding up analysis time shelf life. ASLT method used in determining the shelf-life reed roots extracts beverage using the parameter values of acidity (pH) and color (brightness). reed roots extracts beverage stored for 35 days, at a temperature of 20oC, 30oC and 40oC. From the Arrhenius model calculations with values obtained Ea (activation energy) for the parameters pH value of 9010.68 cal/mol, while the color parameters (brightness) of 4110.16 cal/mol, then the parameters used as the basis for determining the shelf life of reed roots extracts beverage is a parameter that has the smallest activation energy value, ie parameter color value (brightness). Shelf life of reed roots extracts beverage estimated  for 44 days at 27oC and 41 days at 30oC.